Bimodal Pattern of Coronary Microvascular Involvement in Diabetes Mellitus. Issue 11 (November 2016) - Sezer, Murat; Kocaaga, Mehmet; Aslanger, Emre; Atici, Adem; Demirkiran, Ahmet; Bugra, Zehra; Umman, Sabahattin; Umman, Berrin
Abstract : Background: The contribution of functionally disturbed coronary autoregulation and structurally impaired microvascular vasodilatory function to reduced coronary flow velocity reserve, reflecting impaired coronary microcirculation in diabetes mellitus (DM), has not been clearly elucidated. The objective of this study was to identify the mechanism of coronary microvascular impairment in DM in relation to duration of disease. Methods and Results: Coronary flow velocities in the anterior descending coronary artery were assessed by transthoracic echocardiography following angiography revealing normal epicardial coronary arteries in 55 diabetic and 47 nondiabetic patients. Average peak flow velocities, coronary flow velocity reserve, and microvascular resistance in baseline and hyperemic conditions (baseline and hyperemic microvascular resistance, respectively) were assessed. Reduced coronary flow velocity reserve in patients with short duration (<10 years) of DM compared with nondiabetic patients was primarily driven by increased baseline average peak flow velocity (26.50±5.6 versus 22.08±4.31, P =0.008) in the presence of decreased baseline microvascular resistance (3.69±0.86 versus 4.34±0.76, P =0.003). In contrast, decreased coronary flow velocity reserve in patients with long‐standing (≥10 years) DM compared with nondiabetic patients was predominantly driven by reduced hyperemic average peak flow velocity (41.57±10.01 versus 53.47±11.8, P <0.001) due to increased hyperemic microvascular resistance (2.13±0.42 versus 1.69±0.39, P <0.001). Conclusions: Both altered coronary autoregulation and impaired microvascular vasodilatory function contribute to DM‐related coronary microvascular impairment in a time‐dependent manner. DM‐induced early functional microvascular autoregulatory impairment seems to evolve into structural microvascular impairment in the initially overperfused microvascular territory at the later stage of disease.